ANALISIS KEPADATAN JENTIK DENGAN KEJADIAN DBD DI KKECAMATAN SIANTAR UTARA KOTA PEMATANG SIANTAR TAHUN 2025 - Mustar Rusli; NELSON TANJUNG; Th.Teddy Bambang; Deli Syaputri; Samuel Marganda H Manalu (Poltekkes Kemenkes Medan, 2025)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus which is transmitted through the bite of the Aedes aegypti mosquito. Symptoms of DHF include high fever, headache, bone and muscle pain, and signs of bleeding in the skin or other organs. ). Based on data in 2023, there were 177 cases of DHF and 29 cases occurred in the North Siantar District. This disease can affect anyone, but is more common in children and adolescents. DHF is one of the serious health problems in Indonesia because cases continue to increase every year. The high morbidity and mortality rates due to DHF indicate that handling this disease is important and needs to be done seriously. From the DHF problem